A Escrevivência de Conceição Evaristo em Ponciá Vicêncio:encontros e desencontros culturais entre as versões do romance em português e em inglês - Araújo, Rosangela de Oliveira Silva (2012)
This research analyzes Ponciá Vicêncio, a novel by Conceição Evaristo, comparing it to its English version, translated by the Hispanic-American Paloma Martinez-Cruz. Considering the concepts of diaspora, culture and identity, an analysis of the two versions of this novel is developed, so as to highlight the varieties of interpretations arising from the different cultural background in the countries involved. We consider that the concepts mentioned above, inscribed in the field of cultural and post-colonial studies, as well as those of translation theories, constitute essential tools with which to observe the portrayal and reconstruction of the cultural ambience created by Evaristo in her Brazilian Portuguese text and its translation into the context of the English language. For that, we select and analyze cultural linguistic aspects which compose the narrative, comparing the text in Portuguese to its translation in English. Theoretical references to support this analysis are Antoine Berman s (2007) the Analytic of translation, and Lawrence Venuti s (2002) concepts of Domestication and Foreignization. In addition to these, several conceptions of diaspora (and the elements which constitute them), as proposed by Stuart Hall (1998), Homi Bhabha (2007), Stéphane Dufoix (2008), among others, have been used as reference. This study concludes that the choices made by the aforementioned translator are not able to recreate the linguistic and cultural issues existing in the narrative, thus making the translation of Evaristo s Afro-Brazilian novel qualitatively impoverished , as well as perpetuating a tendency, already demonstrated in the texts translated into the English language and culture, of effacing the difference of their others .